STAKEHOLDER ENGAGEMENT IN THE SUSTAINABILITY REPORT OF PT SEMEN INDONESIA TBK - Pangestu, Alfian Dwi; Shahib, Habib Muhammad (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to analyze the form and level of stakeholder engagement in the sustainability report of PT Semen Indonesia (Persero) Tbk. The analysis was conducted on the 2024 ESG report of PT Semen Indonesia and its three subsidiaries. The method used is descriptive qualitative through content analysis using GRI indicators 102-40 to GRI 102-44, as well as classification of engagement levels according to the Morsing & Schultz (2006) and Stocker et al. (2020) models. The results of the study show that the most dominant stakeholder engagement strategy is Level 1 (information strategy) through one-way communication using various media publications, while Level 3 participatory actions are still very limited. These findings confirm that stakeholder engagement is still informative in nature and has not yet reached the level of active collaborative dialogue. This study implies that improving two-way communication strategies is necessary to strengthen the company's legitimacy, accountability, and long-term sustainability